Sylwia Adamczak‑Krysztofowicz / Anna Szczepaniak‑Kozak / Paweł Piotr Rybszleger (Hrsg.). Angewandte Linguistik – Neue Herausforderungen und Konzepte. Festschrift für Izabela Prokop zum 70. Geburtstag. Göttingen: Vandenhoeck & Ruprecht. 2020. S. 453 - Miłosz-Szewczyk, Karolina (Glottodidactica, 2022)
This article is a scientific review of the book „Angewandte Linguistik – Neue Herausforderungen und Konzepte” edited by Sylwia Adamczak-Krysztofowicz, Anna Szczepaniak-Kozak and Paweł Rybszleger on the occasion of the 70th birthday of Professor Dr habil. Izabela Prokop. Numerous interesting contributions were presented in the volume, which are inscribed in the seven thematic areas of pragma and sociolinguistic studies, contrastive studies, interculturality, language acquisition and language teaching research, specialized languages, translation and interpreting, linguistic landscapes and the puriut of the current research questions of Applied linguistics.